(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
The aim of the study was the analysis of the association between ABO blood groups and the prevalence of gall stone disease. 400 patients (250 female and 150 male) of cholelithiasis who had undergone laproscopic cholecystectomy and 400 (250 female and 150 male) healthy subjects were studied as control group. This study did not reveal significant statistical correlation between the distribution of ABO blood group and the prevalence of gall stone disease J. Dhaka National Med. Coll. Hos. 2014; 20 (02) : 3-5